The tourism transition of a “village resort”. Multipositionality and land management in Champéry (Valais), 1870-1970 - Luigi Lorenzetti; Daniela Delmenico (Revue de Géographie Alpine)
Since the 1960s, Switzerland has introduced a series of norms aiming to curb access to real estate ownership by individuals not resident in the country. Concerning mainly tourist localities, these norms were enforced when tourism in Valais was changing from a model based on the provision of hotels to one increasingly oriented toward owning second homes. The case of Champéry suggests that this transition was the result of a double movement: on one hand, the dwindling of multipositionality which, when the tourist industry was born, had tied the economic interests of local tourism to the local political life; on the other hand, the opening up of the land and real estate market resulting in the transfer of ownership to stake-holders outside the community. The municipal development plan of 1969 reflected the desire to preserve the image of Champéry as a “village resort”; a desire that was also demonstrated by the choices of local residents concerning the land and real estate market.